Retinal Glial (Müller) Cells: Sensing and responding to tissue stretch - Lindqvist, Niclas; Liu, Qing; Zajadacz, Joachim; Franze, Kristian; Reichenbach, Andreas (Investigative Ophthalmology & Visual Science, 2010)
Purpose. To test whether Müller glial cells sense, and respond to, mechanical tension in the retina. Methods. A device was designed to stretch the retina at right angles to its surface, across retinal layers. Pieces of retina were mounted between two hollow tubes, and uniaxial force was applied to the tissue using a micrometer-stepping motor. Müller cells were selectively stained with the fluorescent, calciumsensitive dye X-Rhod-1 and were monitored in real time during retinal stretch in vitro. Immunohistochemistry was used to study protein levels and activation of intracellular pathways in stretched retinas. Results. Müller cells responded acutely with transient increases in fluorescence during stretch, indicative of increased intracellular calcium levels. All the Müller cells elongated uniformly, and there was no apparent difference between retinal layers in resistance against mechanical deformation. After stretch, Müller cells showed fast activation of extracellular signal-regulated kinase (after 15 minutes), upregulation of transcription factor c-Fos (after 1 hour), and basic fibroblast growth factor (after 3 hours). No changes in intermediate filament protein expression were observed in Müller cells up to 3 hours after stretch. Conclusions. A novel technique was developed for real-time monitoring of Müller cells during retinal stretch, which allowed the identification of Müller cells as a mechanoresponsive cell type. Mechanical stress triggers molecular responses in Müller cells that could prevent retinal damage. © Association for Research in Vision and Ophthalmology.
CRIS-Team Scopus Importer:2020-08-12